2021
DOI: 10.1186/s12959-021-00353-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of antithrombotic prescription in atrial fibrillation patients with acute coronary syndrome or percutaneous coronary intervention and the subsequent impact on long-term outcomes: a longitudinal cohort study

Abstract: Objectives The choice of optimal antithrombotic therapy in atrial fibrillation (AF) patients with acute coronary syndrome (ACS) or percutaneous coronary intervention (PCI) remains controversial. The aim of this longitudinal cohort study is to investigate the prescribing pattern of antithrombotic regimen in different cohorts and its subsequent impact. Setting and design Longitudinal data from the Tri-Service General Hospital-Coronary Heart Disease (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, this trend stayed validated after adjusting for confounders, namely, AF type, CAD type, and treatment type, factors in the CHA2DS2-VASc score. This phenomenon demonstrated that clinical practice has been influenced by evolving evidence and guidelines recommendations, which is in line with the result from Taiwan (33). This paradigm shift in prescribing practice has been driven in part by the prevalence use of NOACs with a better risk-to-benefit ratio of NOAC-based DT than VKA-based TT (34).…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, this trend stayed validated after adjusting for confounders, namely, AF type, CAD type, and treatment type, factors in the CHA2DS2-VASc score. This phenomenon demonstrated that clinical practice has been influenced by evolving evidence and guidelines recommendations, which is in line with the result from Taiwan (33). This paradigm shift in prescribing practice has been driven in part by the prevalence use of NOACs with a better risk-to-benefit ratio of NOAC-based DT than VKA-based TT (34).…”
Section: Discussionmentioning
confidence: 60%